Relationship Between Middle Ear Total Pressure and Eustachian Tube Function in Otitis Media with Effusion in Children - Utahashi Hiroya; Hamada Yukio; Uchimizu Hirotaka; Tsuji Tomihiko; Mitani Yukie; Aoki Kazuhiro; Moriyama Hiroshi (Otology Japan, 2003)
Otitis media with effusion (OME) is characterized by prolonged inflammation of the middle ear mucosa and it is thought that improvement of OME requires improvement of the middle ear mucosa. We investigated the change in the total middle ear pressure (TMEP) that accompanied with gas exchange, and it was surmised that the TMEP reflected the status of the middle ear mucosa and was capable of serving as an index for predicting the outcome of patients with OME. On the other hand, it was thought that poor eustachian tube function was an important causative factor of OME, and sonotubometry has used as a noninvasive test method for evaluating the pathological state of OME. We investigated OME patients to determine the changes in the TMEP due to treatment with middle ear ventilation tubes, the changes in eustachian tube function as shown by sonotubometry and the clinical course after removal of the tube.The subjects consisted of 70 ears of 70 children (49 males, 21 females) aged 3-15years with OME and in whom the course was able to be followed after removal of the tubes. The ears were divided into two groups based on the clinical course after tube removal: 47-ears in “good” group and 23-ears in “poor” group. Analysis revealed that the duration of the indwelling tube had been significantly longer in the “good” group. The TMEP showed a tendency to increase after intubation, reaching a maximum value after 19 or more months. At the time of tube removal, the maximum TMEP was significantly higher in the “good” group compared with the “poor” group. It was thus surmised that the maximum TMEP reflected the status of the middle ear mucosa, and that this parameter can be used in prediction of the outcome of OME. In addition, sonotubometry showed the eustachian tube function to be significantly more improved in the “good” group than in the “poor” group. In addition, the improvement in the eustachian tube function was significantly greater in patients who had undergone adenotomy. It was concluded that not only long-term use of ventilation tubes but also adenotomy were useful for improvement in OME.